Review of the Psychometric Evidence of the Perceived Stress Scale - Eun-Hyun Lee, RN, PhD (Elsevier, 2012)
Purpose: The purpose of this study was to review articles related to the psychometric properties of the Perceived Stress Scale (PSS). Methods: Systematic literature searches of computerized databases were performed to identify articles on psychometric evaluation of the PSS. Results: The search finally identified 19 articles. Internal consistency reliability, factorial validity, and hypothesis validity of the PSS were well reported. However, the test-retest reliability and criterion validity were relatively rarely evaluated. In general, the psychometric properties of the 10-item PSS were found to be superior to those of the 14-item PSS, while those of the 4-item scale fared the worst. The psychometric properties of the PSS have been evaluated empirically mostly using populations of college students or workers. Conclusion: Overall, the PSS is an easy-to-use questionnaire with established acceptable psychometric properties. However, future studies should evaluate these psychometric properties in greater depth, and validate the scale using diverse populations.